Acercamiento a la poesía religiosa de la etapa colonial centroamérica siglos XVI y XVII desde: Sor Juana de Maldonado y Paz, Baltazar de Orena y Eugenio Salazar de Alarcón - Calvo Oviedo, Marlen (2006)
This paper consists of a brief approach to the Central American literary production in the area of the lyric gender in the XVI and XVII centuries, during which the colonization took place. To achieve the objective, we have dealt write different theoretical texts that have also investigated the same problem. Just like other studies on this field, we have met different positions regarding not only the authors of the texts but also their supposed existence, such is the specific case of Sor Juana de Maldonado y Paz. The aim of this document is to contribute to future researchers. Since most of the production has been written in Guatemala, we attach a corpus of representative authors of that gender period, for in Costa Rica the topic is not well known.